2010
DOI: 10.21273/horttech.20.4.758
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings on the Correlation between Water-soluble Carbohydrate Content in Stolons and First Year Green-up of Seeded Bermudagrass Cultivars

Abstract: Warm-season grasses are not widely accepted in Mediterranean countries because they lose color during the winter months. A study was conducted at the University of Padova (Padova, Italy) to determine whether fall and spring water-soluble carbohydrate (WSC) content in stolons of seeded bermudagrass cultivars (Cynodon dactylon) influenced spring green-up in the first year of establishment. Nine bermudagrass cultivars (La Paloma, Mohawk, NuMex Sahara, Princess 77, Riviera, SR 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
4
25
4
Order By: Relevance
“…These results differ from those of Macolino et al. () and Rimi et al. () who reported that a high water‐soluble carbohydrate content is needed in bermudagrasses for a faster green‐up.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…These results differ from those of Macolino et al. () and Rimi et al. () who reported that a high water‐soluble carbohydrate content is needed in bermudagrasses for a faster green‐up.…”
Section: Resultscontrasting
confidence: 99%
“…Our results indicate that “Princess 77” exhibited a higher carbohydrate content than “Sea Spray” even at the same fertility rate and also greened‐up faster than “Sea Spray” (unpublished data). Our findings do not appear to support the theory of the importance of higher carbohydrate content for faster green‐up reported by others (Macolino et al., ; Rimi et al., ), but they indicate that species and management practices are important factors influencing green‐up. Based on our results, we found no evidence to support our original assumption that carbohydrate content and subsequent green‐up could be influenced solely through fertilization practices.…”
Section: Resultscontrasting
confidence: 99%
“…The green‐up pattern of bermudagrass reported by Macolino et al . () and Rimi et al . () are similar to the green‐up pattern in ‬our study: the rate of change in green color was greatest when the green‐color percentage was between 20 and 80%.…”
Section: Resultsmentioning
confidence: 86%
“…Macolino et al . () found that bermudagrass cultivars, which green up quickly had higher water soluble carbohydrate content. More soluble sugars in stolon and rhizomes ensured earlier green up.…”
Section: Resultsmentioning
confidence: 99%
“…Species and variety selection can help shorten the dormancy period and increase market acceptance of warm‐season grasses in transitional climate zones with long winter periods. For example, seashore paspalum has been shown to provide green colour longer in the fall than bermudagrass (Rimi, Macolino, Richardson, Karcher, & Leinauer, ) and Macolino, Serena, Leinauer, and Ziliotto () reported that the green‐up of the bermudagrass cultivar “Yukon” was faster in the spring than “Princess 77.” Both studies were conducted in northern Italy, in a Mediterranean climate. Furthermore, certain aspects of turfgrass maintenance such as fertilization, mowing and type of irrigation can also affect quality, colour and dormancy and should be considered when turfgrasses are evaluated for length of dormancy.…”
Section: Introductionmentioning
confidence: 99%